Enhancing insolvency frameworks to support economic renewal - André, Christophe (OECD Publishing, 2022)
This paper updates of the OECD Insolvency framework indicator, which summarises the main features of insolvency systems, with respect to their ability to prevent the failure of viable firms, allow a timely exit of non-viable companies, facilitate corporate restructuring and promote entrepreneurship by offering a second chance to honest failed entrepreneurs. The indicator covers 45 countries, including all OECD and European Union members. Since the indicator's previous vintage (2016), most countries have enhanced their insolvency frameworks, notably early warning systems and pre-insolvency procedures. There is still room for improvement, particularly on simplified frameworks for small businesses, which are still often lacking. However, many countries report future insolvency reform plans. The paper also highlights the importance of efficient insolvency procedures as pressure on businesses arises from the gradual withdrawal of COVID-related policy support, the rise in energy costs and interest rates, along with the restructuring needs induced by the green and digital transitions
Keywords: Economics